Maternal and Fetal outcomes in Premature Rupture of Membranes - Kainaat; Naz, Ambreen; Naz, Farah; Mumtaz, Anum; Malik, Rabail; Kubra; Raishem (Indus Journal of Bioscience Research, 2025)
Objective: This study aimed to evaluate the maternal and fetal outcomes associated with term premature rupture of membranes (PROM), with a focus on identifying clinical and laboratory factors that contribute to adverse outcomes. The goal was to determine the impact of PROM-to-delivery interval, infection markers, and delivery mode on neonatal and maternal complications. Methodology: This descriptive cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Peoples University of Medical and Health Sciences for Women (PUMHSW), Nawabshah, over six months (November 02, 2023 to May 01, 2024). A total of 50 women with confirmed term PROM were enrolled using non-probability purposive sampling. The Inclusion criteria were singleton pregnancies at ≥37 weeks of gestation with spontaneous rupture of membranes before the onset of labor. Exclusion criteria included multiple gestation, known fetal anomalies, and preterm PROM. Data was collected using a structured proforma and analyzed using SPSS. Descriptive and inferential statistics were used to explore trends and test associations between variables, with p<0.05 considered statistically significant. Results: The mean age of participants was 28.36 ± 4.59 years, with most being multigravida. The average gestational age was 38.86 weeks. Spontaneous vaginal delivery occurred in 76% of cases, while cesarean section was performed in 24%, primarily due to fetal distress. A prolonged PROM-to-delivery interval (>18 hours) was significantly associated with maternal complications, including chorioamnionitis (30%) and postpartum endometritis (48%) (p<0.05), as well as neonatal sepsis (64%) and stillbirth (22%). CRP positivity (26%) and leukocytosis (36%) were strong predictors of infectious morbidity. Discolored liquor was significantly associated with fetal distress and NICU admissions. Statistical analysis revealed PROM duration, positive inflammatory markers, and abnormal liquor as significant predictors of adverse outcomes (p<0.05). Conclusion: PROM, even at term, presents a substantial risk for maternal and neonatal morbidity when not managed promptly. The findings underscore the importance of early hospital presentation, timely induction of labor, and routine screening for infection using CRP and leukocyte count. Public health initiatives should focus on educating pregnant women about the signs and risks of PROM. Institutional protocols must be strengthened to standardize the management of PROM, particularly in low-resource settings. Further multi-center research with larger sample sizes is needed to explore microbiological factors, optimize intervention timing, and reduce preventable maternal and neonatal complications.